AFIKSASI KATA KERJA DALAM NOVEL NORTHANGER ABBEY OLEH JANE AUSTEN - Pauwah, Siti Haryanti; Pamantung, Rina P.; Sigarlaki, Stephani J. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2022)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â ABSTRACTÂ  Â  Â Siti Haryanti PauwahÂ¹ Dr. Rina P. Pamantung, M.HumÂ² Stephani J. Sigarlaki, S.S, M.HumÂ³ The research, entitled â€œAffixation of Verb in Novel Northanger Abbey by Jane Austenâ€ was written as a study to describe and analyze inflectional and derivational affixes in terms of form, function, and meaning in verbs. This research uses a descriptive method. The data were taken from the novel Northanger Abbey by Jane Austen (1983) then, by identifying, classifying, and analyzing inflectional affixes and derivational affixes according to their form, function, and meaning using the theory of O'Grady and Dobrovolsky (1997). The results of this study are, there were 7 types of verb affixation in the Novel Northanger Abbey novel, namely, prefixes /-de/, /dis-/, and /re-/, and suffixes /- es/, /-ing/, /-ed/, and /-en/. Based on function, inflection affix and derivation affix. Inflection affixes that express the meaning of the third person singular the suffix /-es/ is 11 words. Inflectional affixes that express the meaning of progressive the suffix /-ing/is 11 words. Inflectional affixes that express the meaning of the past tense the suffix /-ed/is 8 words. While the derivational affixes that were found consisted of 10 prefixes and 1 suffixes. Derivation affixes which express the meaning of doing something or causing something, suffix /-en/ is 1 word. Derivation affixes that express the meaning of lowering or opposite to the basic prefix /de-/ is 2 words. Derivation affixes that express the meaning of no, the opposite or the opposite of the word attached to the prefix /dis-/ is 6 words. Derivation affixes that express meaning again, repeat or return the prefix /re-/ is 2 words. Theoretically, this research is expected to provide insight in the field of morphology, especially in verb affixation. Practically, this research can increase the knowledge of readers who want to know about affixation, especially verb affixation in the novel Northanger Abbey. As well as for students who want to deepen their understanding of verbs in English, especially students of the English Department, Faculty of Humanities, University of Sam Ratulangi to get more information about verb affixation and for improvement research. ______________________________Keywords: Affixation, Verb, Prefix, Suffix, Descriptive, Novel Northanger Abbey.